Graiurile poloneze din Poiana Micului şi Bulai (Bucovina de Sud) – o perspectivă sociolingvistică de tip comparativ pe baza ALAB - Olariu, Florin-Teodor; Olariu, Veronica (Studia Romanica Posnaniensia, 2020)
The Polish communities from Bukovina have been studied in the last period through several research projects, initiated by both Polish and Romanian researchers. One of them is the Audiovisual Linguistic Atlas of Bukovina (ALAB), which aims to realize a radiography in multimedia format of the ethnolinguistic diversity of Bukovina. Regarding the Polish ethnic minority, in 2016 two field studies have been carried out in two localities: Bulai and Poiana Micului. Following the analysis of the material thus obtained, we managed to capture some characteristics both at the linguistic and the sociolinguistic level that individualize the two communities. Thus, from a linguistic point of view, the two dialects are different both at phonetic and lexical level, the Bulai dialect being more similar to the Polish literary language. At the sociolinguistic level has been observed the presence of a strong epilinguistic component in the Polish people speech, based on the representations and the attitudes that the Polish ethnic groups have regarding the status and the vitality of their own dialects.